Evaluation of metabolic reactivity in macrophages from mice with chronic sodium arsenite intake and experimental carcinogenesis - Palmieri, Mónica A; Tasat, Deborah R; Molinari, Beatriz L (Cellular and Molecular Biology, 2018)
Arsenic is carcinogenic to human beings, and environmental exposure to arsenic is a public health issue that affects large populations around the world. Thus, studies are needed to determine the mode of action of arsenic and to prevent harmful effects that arise from arsenic intake. In particular, knowledge of the effects of arsenic exposure in individuals who are undergoing a carcinogenesis process is lacking. The present study was performed in mice to evaluate the effect of chronic As3+ administration on peritoneal and alveolar macrophages; the As3+ was administered in drinking water over 9 months and there was a two-stage carcinogenesis process. At the end of the experiment, the number of tumors stabilized to below the control values, but the tumors showed increased malignancy. Our objective was to evaluate the systemic effects of chronic As3+ingestion in a population of macrophages that was derived from the peritoneal cavity and the broncho-alveolar trunk of cancerized mice since they are the first line of defense in the immune system. The results showed that the macrophages under all conditions retained their ability to self-regulate their metabolic reactivity. This feature was more evident in peritoneal macrophages than in alveolar macrophages. Furthermore, an increase in the number of macrophages from animals receiving higher doses of As3+ compared to untreated animals was observed. These findings indicate that certain parameters associated with two-stage skin carcinogenesis are modified by the presence of As3+ in drinking water.